Advocacy in Agricultural Social Movements: Exploring Facebook as a Public Relations Communication Tool - Courtney Meyers; Erica Irlbeck; Mica Graybill-Leonard; David Doerfert (Journal of Applied Communications, 2011)
Public relations is the act of building and maintaining mutually beneficial relationships among organizations and people through the use of marketing and promoting strategies to build and maintain a successful public image. Currently, social media (including Facebook) are being adopted as a communication tool in public relations efforts to build relationships with different publics. Facebook is a popular social networking site that has the capability to offer a range of promotional tools and allows users to build relationships. The purpose of this study was to determine how administrators of Facebook groups are utilizing Facebook for promoting their agricultural advocacy campaigns. Eight semi-structured interviews were conducted with Facebook group administrators who actively contribute to the promotion of a cause by using the social networking site. Results indicated that administrators believe Facebook has been an effective form of communication and that people join their groups primarily to engage in conversations about agriculture and to build relationships with people who share similar interests. Overall, participants were pleased with the outcome of their Facebook groups and offered advice for future practitioners who want to use social media to promote agricultural social movements. The results of this study also led to the development of a model to illustrate how Facebook can be used to promote social movements in agriculture.
Keywords: social movement; social media; Facebook; interviews; online communication; public relations